2013
DOI: 10.1099/mic.0.063784-0
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli toxin gene hipA affects biofilm formation and DNA release

Abstract: Toxin-antitoxin (TA) systems in Escherichia coli may play a role in biofilm formation, but the mechanism involved remains debatable. It is not known whether the TA systems are responsible for extracellular DNA (eDNA) in biofilms. In this study, we investigated the function of the hipBA TA system in biofilm formation by Escherichia coli strain BW25113. First, the deletion of the HipBA TA system in E. coli BW25113 significantly reduced the biofilm biomass without antibiotic stress. Second, treatment of the BW251… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
0
32
0
2
Order By: Relevance
“…Another difference relates to a contribution of these TAs to biofilm formation. For example, Zhao et al (2013) showed that HipAB plays a significant role in biofilm development through extracellular DNA (eDNA) release, a property not associated with MazEFor DinJYafQ-mediated cell death (Kolodkin-Gal et al, 2009). Finally, the common presence of the hipAB locus in B2 and B1 strains may be associated with auxiliary regulation of 33 diverse genes, including those associated with metabolism, transportation, transcriptional regulation and mismatch repair (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another difference relates to a contribution of these TAs to biofilm formation. For example, Zhao et al (2013) showed that HipAB plays a significant role in biofilm development through extracellular DNA (eDNA) release, a property not associated with MazEFor DinJYafQ-mediated cell death (Kolodkin-Gal et al, 2009). Finally, the common presence of the hipAB locus in B2 and B1 strains may be associated with auxiliary regulation of 33 diverse genes, including those associated with metabolism, transportation, transcriptional regulation and mismatch repair (Lin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of CsgD causes decreases in the signalling nucleotide c-di-GMP and curli production, which subsequently reduces biofilm formation. In addition, HipA releases extracellular DNAs that contribute to biofilm adhesion [39], and the TA modules of E. coli , YefM–YoeB, DinJ–YafQ, and RelBE, are related to biofilm formation in that they are activated by the overexpression of the biofilm inhibitor Hna [40]. …”
Section: Biological Roles Of Ta Systemsmentioning
confidence: 99%
“…In E. coli , exposure to ciprofloxacin increased TisB toxin levels and, in parallel, increased persister cell numbers [16]. However, the most direct evidence for a role of TA modules in persister cell formation is derived from studies showing that mutations in the HipBA TA system of E. coli can modulate the frequency of persister cell formation [1719]. Similarly, in M. tuberculosis it has been reported that inactivation of the RelE genes influences the frequency of persister cell formation [20].…”
Section: Introductionmentioning
confidence: 99%